Peningkatan Hasil Belajar Pada Materi Konsekuensi Pewartaan Yesus Melalui Model Pembelajaran Discovery Learning Kelas VIII Mandiri SMPS Bunga Mawar Kota Gunungsitoli - Selvia Sarumaha (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education plays a very important role in efforts to improve the quality of human resources. So, in the world of education teachers must try to help students obtain good learning outcomes. One of the mandatory education in schools is religious education (Catholic Religious Education). Catholic Religious Education in schools is an educational program that instills Christian values ​​through the learning process and also as a means of forming individuals who believe and are devoted to TYME. The direction of the Catholic Religious Education subject seeks to adapt to the needs of the project-based Independent Learning Curriculum to strengthen the achievement of the Pancasila student profile which is always student-centered. Therefore, teachers and researchers apply the Discovery learning model in their learning process in the classroom in order to improve student learning outcomes.The purpose of this research is to find out what the Discovery Learning learning model is and how it is applied in the learning process. This research uses classroom action research methods. The target is class VIII students at SMPS Bunga Mawar Gunungsitoli with material on the consequences of preaching Jesus. After conducting research, researchers discovered an important thing that the Discovery Learning method can arouse students enthusiasm for learning, make students more independent and responsible for their learning obligations well, and students are able to obtain good learning results.